Serological and Pathogenic Analyses of Fowl Adenovirus Serotype 4 (FAdV-4) Strain in Muscovy Ducks - Xianglong Yu; Xianglong Yu; Xianglong Yu; Zhenzhong Wang; Zhenzhong Wang; Zhenzhong Wang; Hao Chen; Hao Chen; Hao Chen; Xiaoyu Niu; Xiaoyu Niu; Xiaoyu Niu; et al. (Frontiers in Microbiology, 2018)
Hydropericardium hepatitis syndrome (HHS) is a lethal disease caused by Fowl adenovirus serotype 4(FAdV-4) that mainly infects 3- to 6-week-old broiler chicks. In 2015, an infectious disease characterized similar symptom to HHS in broilers outbroke in commercial duck flocks in Shandong province. FAdV-4 was isolated from naturally infected ducks and determined by polymerase chain reaction (PCR) amplification and DNA sequence analysis. In order to investigate the effect of FAdV-4 infection on muscovy ducks, we determined and characterized the FAdV-4 Isolate, and assessed its pathogenicity. In this study, HHS was respectively reproduced in 5-week-old muscovy duck by intramuscular injection and intranasal inoculation of allantoic fluid containing FAdV-4, ducks in the negative control group were inoculated with allantoic fluids of healthy duck embryos in the same manner. Clinical symptoms, gross and microscopic lesions, cytokines and antibodies, blood biochemical indices were detected and recorded for 12 days after infection. Typical hydropericardium and hepatitis was observed in experimental muscovy duck in the 3rd day post-inoculation (dpi). FAdV-4 can be replicated in tissues and cause pathological damage, especially in the liver and immune organs. Most of the immune-related cytokines and antibodies levels are up-regulated and then decreased, which may be caused by the initial infection and the normal immune response, later the virus caused the immunosuppression and led to the decrease of levels. To the best of our knowledge, this is the first systematic trial of the pathogenicity of FAdV-4 in muscovy ducks mainly based on the serological test, which will provide new insights into the study of the disease.